Cross-Gender Interpersonal Meaning in Banking Product and Service Offerings - Leonita Maharani (CV. Rayyan Dwi Bharata, 2022)
This study examines the realization of interpersonal meaning through the speech function of offering products and services carried out by male and female Customer Service Representatives in banking service activities. Although in the results of the study, it was found that the similarity of the dominant mood type was used, it was concluded that male and female CSR realized interpersonal meanings differently. This can be seen from the emergence of imperative forms by male CSR and the dominant use of my subject compared to other subjects as well as types of High Modalities, compared to female CSR which uses more product name subjects and medium modalities in offering banking products and services to their customers. The results of the study concluded that when offering products and services to customers, A man's CSR tends to show its identity as mentioned in gender theory, namely speaking with authority, direct, and placing oneself as a superior party, while female CSR in addition to offering products and services she also tends to show a desire to establish close relationships with her customers.